Chapter «Di pietra un Villanel, che da lontano par vivo»: il Villano con la falce di Valerio Cioli nel giardino mediceo di Pratolino - Sisi, Alessia (Studi e saggi, 2020)
In the second half of the 16th century, in the garden of the Medicean villa of Pratolino the sculptor Valerio Cioli created, among other groups, the Villano con la falce, which represented a peasant in the act of sawing the reeds in a marshy lake where there was a salamander that spurted water from its mouth. The salamander is now lost while the Villano has been identified so far by critics with the statue of the so-called Mietitore attributed to Cioli and now in the Boboli garden deposits. In the 1990s, during restorations at Pratolino, a stone fragment of a male statue was found: through a careful analysis of the documentary and figurative sources as well as a close comparison with other works certainly by Cioli, this paper aims to recognize the fragment as the Villano con la falce.